The The impact of externalization of border controls on the human rights of refugees in the Italian-Libyan Mediterranean Sea - Baron, James; Saragih, Hendra Maujana (Universitas Islam Malang, 2023)
The issue of the high mortality of immigrants related to violations of international law is not an easy discourse. Failure to do so, both in scholarship and in activism towards human rights, shows significant limitations and hurdles of international law and international relations specifically in addressing human rights for refugees. This study aims to address and shine a light on the problem that migrant poses in the Mediterranean Sea. In the wake of the migration crisis, European Union in particular Italy adopted a series of policies in order to reduce migration flows within the EU. This article uses methods qualitative research methodology with a focus on conducting an in-depth literature review. The findings present that an ambitious policy to reduce the flow of migrants was introduced to combat the surge of refugees, an example of these steps is the Italian-Libyan Memorandum of Understanding of 2 February 2017 which led to questions about the ability of the state to uphold their roles and obligation in addressing human rights for refugees that caused twenty more people died at the Mediterranean Sea. This article examines the challenges posed by the refugees that have been caused by the treaties in force at the Mediterranean Sea as well as specific issues regarding the monitoring and implementation of the above regulations, which cause obstacles and challenges that impact the life and the migration process of refugees. Through this article we also highlighted that one of the most important motives in migration from Libya to Italy is economic opportunities for migrants, hence further studies are necessary in resolving the ongoing dispute.